Drying of pistachios by using a microwave assisted dryer - doi: 10.4025/actascitechnol.v35i2.14798 - Balbay, AsÄ±m; Åžahin, í–mer (Acta Scientiarum. Technology, 2012)
In this study, the drying kinetics of two varieties of Turkey pistachios (Antep- Moisture content (MC) 32.01% (db) and Siirt-MC 41.92% (db)) were investigated by using a temperature and power controlled microwave dryer. The drying experiments were carried out at different temperatures (36, 40 and 48Â°C), air flow rates (FRs) (0.2, 0.4 and 0.7 m3 h-1) and microwave power (250, 500 and 750 W).Â Six mathematical models in the literature were selected to the determination of the goodness of fit based on the experimental data. Among the selected models, the Modified Henderson and Pabis model was found to be the optimum model for describing the drying behavior of Antep pistachios (APs) and Siirt pistachios (SPs). It was found that R2 values for both APs and SPs were found between 0.992 and 0.9999. Â